(untitled) (Czech Journal of International Relations, 2003)
Steven J. Brams: Negotiation Games. Applying Game Theory to Bargaining and Arbitration. 1st revised ed. Routledge, London 2003, 26 + 297 s., ISBN 0-415-30895-X.